Optimization of the production of lovastatin from Aspergillus sclerotiorum PSU-RSPG178 under static liquid culture using response surface methodology - Sudarat Suwannarat; Jutarut Iewkittayakorn; Yaowapa Sukpondma; Vatcharin Rukachaisirikul; Souwalak Phongpaichit; Wilaiwan Chotigeat (Penerbit Universiti Kebangsaan Malaysia, 2019)
The effect of lovastatin on cholesterol synthesis is well known. Although lovastatin has been produced from several Aspergillus species and cultivation systems, the yield of lovastatin from Aspergillus sclerotiorum PSU-RSPG178 in a static liquid system has not yet been determined. Therefore, the objective of this study was to optimize lovastatin production from this strain using a central composite design developed through response surface methodology (RSM). The inoculum was prepared from mycelium or spore cultured in static liquid and shaking systems with potato dextrose broth (PDB) as the medium. The best inoculum preparation and cultivation systems were selected to study the optimization of the four fermentation parameters of medium concentration (X-5X), temperature (25-37°C), culture medium to flask volume ratio (2.5-12.5) and time (7-35 days). The best inoculum preparation was the mycelium method and the best cultivation system was the static liquid system. In the optimization procedure, a yield of 1315.69 mg/L lovastatin was obtained at a PDB concentration of 5X, a temperature of 25°C, a medium to flask volume ratio of 1:2.5 and a time of 21 days. In a model employing the optimized parameters, temperature was found to have the most effect on lovastatin production, which will decrease if temperature increases above 25°C. Based on this study, A. sclerotiorum PSU-RSPG178 can be a useful strain for producing lovastatin and RSM as an optimization technique not only reduced the number of experiments but also resulted in an optimized lovastatin yield.